Differences in Physical Activity, Lactic Acid Concentration, and Quality of Life between Gender among First Year Medical Students (Majalah Kedokteran Bandung, 2019)
Medical students have fewer opportunities to do physical activities (PA) that may increase the risk for chronic diseases. The aim of this study was to assess the correlation between PA, as assessed using the International Physical Activity Questionnaire (IPAQ), and Lactic acid (LA) concentration, as well as the differences in IPAQ, LA, and quality of life (QoL) between genders. This was a cross-sectional study conducted in April - November 2017 by a private university in West Jakarta. Subjects of the study were selected using simple random sampling approach with female subjects as the more dominant gender ( n=76, 60%) from the 126 subjects recruited. The median of IPAQ, La- 1, and La-2 in male and female were 707 (474–944) vs 423 (392–501) Mets (p=0.7), 4.6 (3.8–5.4) vs 2.8 (2–3) mmol/L (p=0.001), and 8.4 (7.7–8.9) vs 10 (9.3-10.5) mmol/L (p
Keywords: Lactic acid; medical students; physical activity; quality of life